2022
DOI: 10.3889/oamjms.2022.9545
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol, Prolactin, and Breastmilk Volume; A Promising Pattern for Reducing Postpartum Depression

Abstract: BACKGROUND: Research shows postnatal depression and shorter breastfeeding are consistently related, but their causal effect remains debatable. To reduce the impact of mental disorders in the perinatal period, lactation may give a significant neuroendocrine effect. AIM: This study aimed to examine hormonal patterns and estimated breastmilk volume of mothers with depression. MATERIALS AND METHODS: This study was conducted during the three-trimester to 6-week postnatal period. It involved 60 pregnant women fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…These findings align with prior research indicating that during the postpartum period, hormonal fluctuations may lead to changes in maternal emotion. 17,28,29 Previous studies have identified three key psychological variables -emotion regulation, maternal self-confidence, and marital satisfaction -that may contribute to psychological breakdowns. Emotion regulation is particularly crucial for managing stress situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings align with prior research indicating that during the postpartum period, hormonal fluctuations may lead to changes in maternal emotion. 17,28,29 Previous studies have identified three key psychological variables -emotion regulation, maternal self-confidence, and marital satisfaction -that may contribute to psychological breakdowns. Emotion regulation is particularly crucial for managing stress situations.…”
Section: Discussionmentioning
confidence: 99%
“…Employing self-talk not only facilitates emotional regulation but also contributes to establishing trust between healthcare professionals and postpartum mothers. 29,37 Furthermore, research underscores the significant correlation between psychological breakdowns, postpartum blues, and their impact on breast milk volume. A study revealed a substantial association between psychological well-being and the quantity of breast milk produced.…”
Section: Discussionmentioning
confidence: 99%